KIChIK MAKTAB YOShIDAGI BOLALARDA EKOLOGIK MADANIYATNI ShAKLLANTIRIShNING PSIXOLOGIK ASOSLARI - Allayarov, M.J. (SCIENCE and SOCIETY, 2025)
The article analyses the psychological foundations of the formation of environmental awareness in primary school children.